2023
DOI: 10.3390/healthcare11071020
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity, Sedentary Behavior and Quality of Life in the Chilean Population: ENCAVI Results, 2015–2016

Abstract: Regular physical activity (PA) is indicated to be one of the main healthy habits that allow populations to achieve a good quality of life (QoL); however, levels of physical inactivity (PI) and sedentary behavior (SB) have risen worldwide, with negative health effects. The aim of this study is to analyze PI and SB levels, as well as their association with QoL in the Chilean population. A secondary analysis was performed based on the database from the 2015–2016 National Quality of Life Survey (ENCAVI) in Chile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…At the same time, recent studies have reported that at least 20 min of moderate-to-vigorous physical activity per day can reduce the prevalence of cardiovascular disease in adults by 16-40% [56,57] and that a physically inactive an active lifestyle will increase the likelihood of chronic non-communicable diseases and increase the risk of cancer, which together raise the risk of death [58]. An American College of Sports Medicine created a physical activity guide chart for different populations based on the intensity and frequency of physical activity, aiming to promote the development of national physical activity habits and the level of national physical health through Fang and Zhang BMC Public Health (2024) 24:1480 this guide [59].…”
Section: Physical Activity and Physical Healthmentioning
confidence: 99%
“…At the same time, recent studies have reported that at least 20 min of moderate-to-vigorous physical activity per day can reduce the prevalence of cardiovascular disease in adults by 16-40% [56,57] and that a physically inactive an active lifestyle will increase the likelihood of chronic non-communicable diseases and increase the risk of cancer, which together raise the risk of death [58]. An American College of Sports Medicine created a physical activity guide chart for different populations based on the intensity and frequency of physical activity, aiming to promote the development of national physical activity habits and the level of national physical health through Fang and Zhang BMC Public Health (2024) 24:1480 this guide [59].…”
Section: Physical Activity and Physical Healthmentioning
confidence: 99%